2009
DOI: 10.4161/derm.1.1.7674
|View full text |Cite
|
Sign up to set email alerts
|

The unfavorable effect of the A allele of the vitamin D receptor promoter polymorphism A-1012G has different mechanisms related to susceptibility and outcome of malignant melanoma

Abstract: The A allele of the A-1012G (rs4516035) vitamin D receptor (VDR) promoter polymorphism is associated with increased susceptibility and worsened outcome in malignant melanoma (MM). The A allele contains a GATA-3 binding site. There is a second polymorphism in the same promoter region, G-1520C (rs7139166), and there is potential for another GATA binding site in the G allele. Here, we tested the hypothesis that the G -1520 A -1012 haplotype might be a greater risk factor for MM than A-1012 alone. The A allele of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Halsall et al found out that the CA haplotype was a very significant risk factor for malignant melanoma while the CG haplotype was protective. 50 There was no effect of GA haplotype. The A allele of A-1012G was more frequent in patients with metastasis than malignant melanoma patients without metastasis, as was the G allele.…”
Section: Vdes and Skinmentioning
confidence: 86%
See 2 more Smart Citations
“…Halsall et al found out that the CA haplotype was a very significant risk factor for malignant melanoma while the CG haplotype was protective. 50 There was no effect of GA haplotype. The A allele of A-1012G was more frequent in patients with metastasis than malignant melanoma patients without metastasis, as was the G allele.…”
Section: Vdes and Skinmentioning
confidence: 86%
“…Futrthermore, Halsall et al tested the hypothesis that the G(-1520)A(-1012) haplotype of the VDR promoter polymorphism might be a greater risk factor for MM than A-1012 alone. 50 The A allele of A-1012G was preferentially linked to G of G-1520C and was more frequent in malignant melanoma patients but G of G-1520C was not. Halsall et al found out that the CA haplotype was a very significant risk factor for malignant melanoma while the CG haplotype was protective.…”
Section: Vdes and Skinmentioning
confidence: 97%
See 1 more Smart Citation
“…The A allele in position 1A-1012 (rs4516035) also contributes to different physiological processes and disorders, and may indirectly promote a GATA-3-driven T-cell switch from naive to T-helper 2 cells; this allele may influence susceptibility and metastasis under the influence of transcription factors secreted by different cellular backgrounds (Halsall et al, 2009). SNPs at the -1012 locus may be correlated with height and serum calcium concentration, in contrast with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…39 Another study involving elderly subjects found significant associations between VDR-BsmI, VDR-TaqI and a low composite cognitive score (calculated by averaging the scores of other cognitive function tests) but not with a low MMSE score. 40 Additionally, a significant association was observed between VDR-ApaI and less (73) 13 (18) 138 (24) 1 (1) 16 (3) 131 ( …”
Section: Discussionmentioning
confidence: 99%